Extraction Of Tannin From Oil Palm Empty Fruit Bunch As A Rust Deactivator. - M. N., Mohamad Ibrahim; M.Y, Nor Nadiah; A.A., Amirul (2005)
The purpose of this research is to investigate the effect of reaction between rust and rust deactivator obtained from oil palm empty fruit bunch (EFB) powder.